2020
DOI: 10.1097/md.0000000000020744
|View full text |Cite
|
Sign up to set email alerts
|

Association between pentraxin-3 and the risk of preeclampsia

Abstract: An association between circulating pentraxin-3 (PTX3) and the risk of preeclampsia (PE) remains to be established. We performed a meta-analysis of observational studies to evaluate their relationship. The PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, and WanFang databases were searched for related observational studies evaluating PTX3 and PE risk. A random-effects or a fixed-effects model was used in the meta-analysis, depending on the heterogeneity among the included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
2
11
1
Order By: Relevance
“…Even though CRP and PTX3 are indeed structurally and functionally related, their production is additionally triggered by different inflammatory stimuli, which probably reflects potential of also diverging biological functions (1,(11)(12)(13). It has been demonstrated that the expression of PTX3 in the peripheral blood is closely related to preeclampsia (19), but no such pregnancy complications has yet been firmly established for CRP (32,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though CRP and PTX3 are indeed structurally and functionally related, their production is additionally triggered by different inflammatory stimuli, which probably reflects potential of also diverging biological functions (1,(11)(12)(13). It has been demonstrated that the expression of PTX3 in the peripheral blood is closely related to preeclampsia (19), but no such pregnancy complications has yet been firmly established for CRP (32,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in PTX3 causes reduced fertility in mice and reduced litter size ( 14 17 ), aligning with data highlighting the importance of PTX3 for implantation ( 18 ). However, increased levels of PTX3 have also been associated with preeclampsia ( 19 , 20 ). It is believed that there is an exaggerated inflammatory response and endothelial dysfunction in preeclamptic pregnancies, resulting in an increased release of inflammatory mediators such as PTX3 ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of these proteins in PE has been previously described. The decrease in RGS2 expression contributes to PE through its inhibitory function on arterial pressure regulation [ 89 ], and PTX3 is involved in the regulation of inflammation and is upregulated in women with PE [ 86 ]. Variants in MTHFR can induce a decrease in the enzymatic activity that increases folate levels, which contributes to PE [ 87 ].…”
Section: Mirnasmentioning
confidence: 99%
“…Pentraxin 3 (PTX3), a member of the c-reactive protein family, is a long pentraxin protein and a pro-inflammatory marker ( 14 ). Under inflammatory conditions, PTX3 is secreted by vascular endothelial cells and monocytes ( 15 ).…”
Section: Introductionmentioning
confidence: 99%